Procedure of definition of structure and parameters of multi-band matching circuits on the basis of intracavitary complex criterion for conformity to the ideal filter - V. N. Shashok; A. S. Kanaplizki (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article gives the procedure of structurally parametric synthesis of multi-band frequency-selective circuits. A short characteristic of approaches to solve the problems of synthesis of the multi-band frequencyselective circuits based on the use of multifrequency resonators, frequency transformations and parametric transformations using numerical procedures of optimisation is given. The research presents a short description of three widely used estimation criteria of the characteristics of frequency-selective circuits: Taylor, Chebyshev and average-degree criteria. Expedients of an estimate of joint approximation of amplitude-frequency and phasefrequency characteristics of synthesized circuits to those of the ideal filter are shown. The criterion is suggested and the procedure is presented for structurally parametrical synthesis of multi-band matching circuits on the basis of intracavitary complex criterion of conformity to the ideal filter in a transmission band and interband Chebyshev criterion realized by numerical optimization of synthesized circuits relative to the chosen criterion for affinessy is given. With that, the multi-band circuit is represented in form of a ladder-type connection that, generally, consists of n different reactive resistances. The example of using the proposed procedure to solve the problem of structurally parametric synthesis of a two-band matching circuit is given. As a matching load we selected the first-type equivalent consisting of a serial connection of active resistance and capacity. In the example there is an additional requirement to ensuring interband frequency selectivity. Such requirement is ensured by introducing zero to the function of transmission of the synthesized circuit on an interband average geometric frequency. The requirement is implemented by introducing a parallel oscillating circuit to the first serial arm of the synthesized circuit. The structurally parametric synthesis of the two-band matching circuit selected in the example is carried out through Mathcad 15 software based on the integrated method of Levenberg-Marquardt optimization.